2022
DOI: 10.3390/ijerph19095478
|View full text |Cite
|
Sign up to set email alerts
|

Adapting a Dementia Care Management Intervention for Regional Implementation: A Theory-Based Participatory Barrier Analysis

Abstract: Dementia is a leading cause of disability and dependency in older people worldwide. As the number of people affected increases, so does the need for innovative care models. Dementia care management (DCM) is an empirically validated approach for improving the care and quality of life for people with dementia (PwD) and caregivers. The aim of this study is to investigate the influencing factors and critical pathways for the implementation of a regionally adapted DCM standard in the existing primary care structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Future research could investigate the integration of our SDM strategy into overall dementia care management (DCM). DCM is a collaborative model of care in which qualified professionals support PwAD and their caregivers in a home setting according to their individual needs [ 37 ]. These professionals could be trained in the assessment of capacity to consent and in the use of SDM to support PwAD in complex decision-making situations.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could investigate the integration of our SDM strategy into overall dementia care management (DCM). DCM is a collaborative model of care in which qualified professionals support PwAD and their caregivers in a home setting according to their individual needs [ 37 ]. These professionals could be trained in the assessment of capacity to consent and in the use of SDM to support PwAD in complex decision-making situations.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies using the CFIR as a theoretical framework, conducted in a long‐term care and a primary care setting, also reported similar findings. Shortage of staff and insufficient time for involvement in implementation activities, together with insufficient engagement and participation (Coffey et al, 2021), non‐readiness within the organisation, as well as a misfit between the organisation and the intervention (Seidel et al, 2022) were identified as main barriers to adoption or reasons for implementation failure.…”
Section: Discussionmentioning
confidence: 99%
“…High staff fluctuations, both within the clinical teams, the champions, as well as the research team, resulted in fractured engagement and diminishing support from the stakeholders. Prior research found that the availability of internal and external support, along with trained facilitators and flexible delivery of training units, were key enablers in dementia training and education programmes (Heward, Board, Spriggs, Blagden, & Murphy, 2021; Surr, Parveen, et al, 2020) when implementing evidence‐based guidance (Coffey et al, 2021; Karrer et al, 2020; Seidel et al, 2022). The fractured engagement processes and lack of skilled facilitation, insufficient training opportunities, particularly in relation to the champions' role, undermined some of the expected benefit of the employed co‐design strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PriDem study across England and Wales notes that despite some financial incentives, GPs may not have the capacity to deliver good quality dementia care ( 23 ). European primary care studies also report problems in GP engagement in delivery of dementia initiatives ( 24 , 25 ). Reasons for fragile post-diagnostic dementia care include fragmentation, poor communication around care pathways and inadequate health and social care policies ( 26 , 27 ).…”
Section: Introductionmentioning
confidence: 99%